Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s12944-015-0014-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of testosterone deficiency on cholesterol metabolism in pigs fed a high-fat and high-cholesterol diet

Abstract: BackgroundTestosterone deficiency is associated with increased serum cholesterol levels. However, how testosterone deficiency precisely affects cholesterol metabolism remains unclear. Therefore, in the current study, we examined the effect of testosterone deficiency on cholesterol metabolism and liver gene expression in pigs fed a high-fat and high-cholesterol (HFC) diet.MethodsSexually mature male miniature pigs (6–7 months old) were randomly divided into 3 groups as follows: intact male pigs fed an HFC diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 48 publications
7
25
0
5
Order By: Relevance
“…We also found significant differences in serum high density 38 who found that the levels of total cholesterol and LDL cholesterol are increased significantly by castration.…”
Section: Discussionsupporting
confidence: 51%
“…We also found significant differences in serum high density 38 who found that the levels of total cholesterol and LDL cholesterol are increased significantly by castration.…”
Section: Discussionsupporting
confidence: 51%
“…Also, animal studies have displayed marked increase in serum TC levels in testosteronedeficient male mice (Hatch et al, 2012). In addition, testosterone depletion led to increase in TC, TG and LDL-c levels in animals (Cai et al, 2015). Interestingly, present study displayed dose dependent decrease in the serum testosterone level (data not shown) accompanied with markedly enhanced concentrations of lipid profile (TC, TG and LDL-c) in FLU-treated rats.…”
Section: Discussionsupporting
confidence: 39%
“…It is likely that an adverse intrauterine environment is better able to affect the neuroendocrine programming of lipid metabolic-related genes of female foetuses in utero . This gender difference may be related to sex hormones, and the different effects of oestrogen and androgen on hepatic cholesterol metabolism might play important roles [42, 43]. For example, low oestrogen levels can cause hypercholesterolemia by inhibiting the expression of hepatic CYP7A1 [43].…”
Section: Discussionmentioning
confidence: 99%